Andersson‐Magnéli Phases TinO2n‐1: Recent Progress Inspired by Swedish Scientists. Issue 2 (10th February 2021) - Zhang, Qing; Liu, Weiyan; Zhou, Yi; Li, Junyan; Sun, Tu; Liu, Qingyuan; Ma, Yanhang; Wang, Jinghui; Li, Jun; Zhao, Ruoshi; Sui, Yu; Matsumoto, Takashi; et al.
Abstract: Among homologous series of metal oxides, Andersson‐Magnéli phases Tin O2n‐1 ( n =4–10) have attracted renewed scientific attention because of their behaviour in electrical conductivity and chemical/thermal stability. Various applications have also been reported for the phases with different values of n, or slightly reduced rutile (TiO2 ). The characteristic properties of these materials depend strongly on the compositional deviation from TiO2 and the way in which the structure accommodates the deviation. Thus, an urgent requirement is to overcome difficulties in characterizing such materials at atomic resolution. Here, we trace the discovery of the Andersson‐Magnéli phases, and report the application of recent developments in electron microscopy to reveal the relation, at the local level, between structural characteristics and electronic states, specifically for the materials Tin O2n‐1 with n =4–8. The electrical conductivity of Ti4 O7 has been reported previously to show three clearly distinct states on decreasing temperature from 300 K. For this reason, we focus on Ti4 O7 as a representative example of the Tin O2n‐1 phases and report structural characteristics at temperatures corresponding to each of the three different phases, focusing on the distribution of Ti 3+ and Ti 4+ cations from analysis of single‐crystal XRD data. Electron diffraction experiments and electrical conductivity measurements are also reported. Abstract :